MUATAN KURIKULUM PENDIDIKAN ISLAM DALAM HADITH JIBRIL: KAJIAN MATERI DAN METODE PEMBELAJARAN - Alawy, Naufal; Syahputra, Gama; Thobroni, Ahmad Yusam (Kuttab: Jurnal Ilmu Pendidikan Islam, 2024)
This article aims to address the issue of curriculum stagnation in Indonesia, which often undergoes changes without yielding significant results. Many Muslim scholars have conducted in-depth research to identify the real problems within the curriculum, particularly focusing on the components of content and methodology. This article employs a literature study research method, gathering both primary and secondary data. The author finds that the curriculum is a learning tool designed to facilitate the educational process in achieving its goals. The curriculum consists of several components, namely objectives, content, methods, and evaluation. Based on the analysis of the Hadith Â of Gabriel, the content components include aqidah (faith), fiqh (Islamic jurisprudence), tasawuf (ethics), and eschatology. Additionally, the method derived from the Hadith Â of Gabriel is the hiwar or dialogue method.